An Approach to Manufacture of Fresh Chicken Sausages Incorporated with Black Cumin and Flaxseed Oil in Water Gelled Emulsion - Kavuşan, Hülya Serpil (Food Sci Anim Resour, 2020)
In order to investigate the use of oil in water gelled emulsion (GE) prepared with healthier oil combinations as beef fat replacer in the fresh chicken sausage formulations, four batches of fresh sausages were produced. The first batch was control (C) sample formulated with %100 beef fat, other batches were codded as GE50, GE75, and GE100 respective to the percentage of beef fat replaced with GE. The addition of GE to sausage formulation resulted in an increment in moisture and protein contents while a decrement was observed in fat content (p<0.05). pH, cooking yield and water holding capacity values of GE added samples were found lower than C (p<0.05). GE addition caused lower CIE L* values in samples, however, this trend was not observed in CIE a* and CIE b* values. Initially, the lowest peroxide and the highest TBARS values were recorded in GE100 samples on the 0(th) d (p<0.05). Peroxide and TBARS values were in the limits. The texture of samples was softened while total saturated fatty acid content reduced up to 52.61% with the incorporation of GE (p<0.05). Taken together, our results showed that GEs can be used as fat replacers in meat product formulations without causing undesirable quality changes.